Calogero Model(s) and Deformed Oscillators - Marijan Milekovic; Stjepan Meljanac; Andjelo Samsarov (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We briefly review some recent results concerning algebraical (oscillator) aspects of the N-body single-species and multispecies Calogero models in one dimension. We show how these models emerge from the matrix generalization of the harmonic oscillator Hamiltonian. We make some comments on the solvability of these models.